Para politikasının bir aracı olarak açık piyasa işlemleri ve Türkiye örneği - Ayrancıoğlu, N. Deniz (My University, 1999)
The first of the policies followed in reaching certain economical aims in economy, is the policy of money. Monetary politics is the attempt to regulate credit conditions and money supply, in order to meet the economic aims set forth by the bank The main aims of money politics can be set forth as ensuring full employment, realising price stability, economic growth and maintaining balance of payments. The main tools money politics in reaching these targets are free trade, rediscount policies, the policy of mandatory returns, and general disponibility. The Central Bank is responsible for money politics. The Central Bank uses free trade procedures, one of the tools of money politics, in order the control cash flow. Free trade politics means the buying and selling of stocks and bonds on the market by the Central Bank, in order to regulate the liquidity of the economy and cash flow. If the Central Bank wishes to increase the cash flow, it buys from the market in free trade buys, thus releasing cash to market; if the aim is to reduce cash flow, it sells some of the stocks and bonds in its portfolio, thus removing some of the money from circulation. Of the money politics tools, free trade procedures have been used in Turkey since the beginning of 1980's T.C. Central Bank has started free trade procedures on February 4, 1987. Money and capital markets in Turkey have started developing about ten years ago. The most important difficulty in applying free trade procedures is the lack of a developed and diversified capital market. On the other hand, the use of free procedures are increasing with time. In order for the free market procedures to be used effectively, the stocks and bonds portfolio of the Central Bank has to be enriched, the money and capital markets have to be developed, and sufficient amounts of financial values must be freely bought and sold in these markets. Turkey will be able to use the free trade procedures successfully, if these conditions are met.

Ekonomide belirli ekonomik hedeflere ulaşmayı sağlayan politikaların başında para politikası gelir. Para politikası, Merkez Bankası tarafından belirlenmiş olan ekonomik hedefleri gerçekleştirmek üzere para arzını ve kredi koşullarını düzenleme çabasıdır. Para politikasının temel amaçları; tam istihdamın sağlanması, fiyat istikrarının gerçekleştirilmesi, ekonomik büyüme ve ödemeler bilançosu dengesinin sağlanması olarak sıralanabilir. Para politikasının bu amaçlara ulaşmak için kullandığı belli başlı araçlar ise; açık piyasa işlemleri, reeskont politikası, zorunlu karşılıklar politikası ve genel disponibilite'dir. Para politikasından sorumlu organ Merkez Bankası'dır. Merkez Bankası, para arzını ayarlamak amacıyla para politikası araçlarından açık piyasa işlemlerini kullanmaktadır. Açık piyasa işlemleri; Merkez Bankası'nın, para arzını ve ekonominin likiditesini düzenlemek amacıyla, piyasadaki mevcut senetleri alıp satmasıdır. Eğer Merkez Bankası para arzını bu yolla arttırmayı amaçlarsa, piyasadan açık piyasa alımları nda bulunulur, böylece piyasaya para çıkarır; eğer amaç para arzını düşürmekse, portföyündeki senet veya tahvillerin bir kısmını satışa çıkarır, bu yolla piyasadan para çeker. Para politikası araçlarından açık piyasa işlemleri ülkemizde 1980'li yılların ortalarından itibaren uygulanmaya başlamıştır. T.C. Merkez Bankası 4 Şubat 1987 tarihinden itibaren açık piyasa işlemleri yapmaya başlamıştır. Ülkemizde para ve sermaye piyasaları yaklaşık on yıldır bir gelişme süreci içine girmiştir. Açık piyasa işlemlerinin uygulanmasının en önemli zorluğu ise gelişmiş ve çeşitlileşmiş bir sermaye piyasasının yokluğudur. Ancak geçen zaman içerisinde açık piyasa işlemlerinin kullanımı hızla artmaktadır. Açık piyasa işlemlerinin etkin bir şekilde kullanılabilmesi için Merkez Bankası menkul değer portföyünün zenginleştirilmesi, para ve sermaye piyasalarının geliştirilmesi, bu piyasalarda yeterli sayıda ve tutarda finansal varlığın serbestçe alınıp satılması gerekmektedir. Bu şartlar sağlandığı taktirde Türkiye'de açık piyasa işlemleri başarılı bir biçimde kullanılacaktır.
Keywords: EKONOMİ; PARA POLİTİKASI